2021
DOI: 10.1002/eji.202048968
|View full text |Cite
|
Sign up to set email alerts
|

Bruton's tyrosine kinase inhibition induces rewiring of proximal and distal B‐cell receptor signaling in mice

Abstract: Bruton s tyrosine kinase (Btk) is a crucial signaling molecule in BCR signaling and a key regulator of B-cell differentiation and function. Btk inhibition has shown impressive clinical efficacy in various B-cell malignancies. However, it remains unknown whether inhibition additionally induces changes in BCR signaling due to feedback mechanisms, a phenomenon referred to as BCR rewiring. In this report, we studied the impact of Btk activity on major components of the BCR signaling pathway in mice. As expected, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
(93 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, it was reported that BTK inhibition increases CD79a phosphorylation as a part of compensation feedback loop. It leads to activation of multiple key BCR signal mediators with consequent proximal BCR signal rewiring [ 177 ]. Increased CD79a/CD79b activity might be one of general resistance mechanisms.…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%
“…On the other hand, it was reported that BTK inhibition increases CD79a phosphorylation as a part of compensation feedback loop. It leads to activation of multiple key BCR signal mediators with consequent proximal BCR signal rewiring [ 177 ]. Increased CD79a/CD79b activity might be one of general resistance mechanisms.…”
Section: Open Questions and Future Directionsmentioning
confidence: 99%